The Role of Media for Communication During the Disaster - Yuliana Yuliana (Jurnal Studi Ilmu Sosial dan Politik, 2023)
Purpose: This paper aims to describe the role of media in communication during the disaster. Research methodology: This paper is a narrative literature review. The articles were taken from Science Direct and Google Scholar. The articles were selected based on the title, abstract, and full-text screening. Results: Results revealed that the roles of media are essential such as making people understand the types of disaster risk, providing information and solution for managing risks, engaging people power, disseminating information, hosting a discussion between government and people, also creating a sharing idea platform, and communicating emotions. Media language and communication type must be well prepared to disseminate the right information at the precise time. In conclusion, the media’s role is essential in disseminating information, solutions, and emotions among people during a disaster. Therefore, the language and communication type must be carefully selected to deliver precise information at the right time. Contribution: Social and disaster management Limitations: The specific media should be determined in a research to compare the role of each media equally.